RESEPSI MUSHAF ALQURAN DAN TERJEMAHNYA TERBITAN SYAMIL ALQURAN EDISI SPECIAL FOR WOMAN: Studi Terhadap Mahasiswi IAIN Syekh Nurjati Cirebon - Wida Hikmatul Lisa; Anisatun Muthi’ah (UIN Siber Syekh Nurjati Cirebon, 2019)
The Qur’an as the source of the highest Islamic teachings at first was not fixated on written narration but verbal transmission. However, with the spread of Islam out of the social and cultural sphere of Arabic, oral transmission is felt to be isufficient to overcome the rapid growth of the Musliim community. Therefore, the Koran develops with the simple writing model. The history of the Qur’anic text does not stop at the codification of manuscripts, but it continues on publishing and printing. One of them is thematic quran which is based on the subject of the reader, such as the Qur’an and its translation published by Syamil Alquran edition special for woman. This research to describe the systematic presentation of the Qur’anic manuscripts and the translation of the issue of the special for woman edition of syamil Alquran and the student reception of the mushaf. Then the method used is qualitative literature and the field with the Hans Robert Jauss reception theory approach.